Problems and prospects of implementing UN action against terrorism - Laborde, Jean-Paul (Journal of international criminal justice, 2010)
The article deals with two related problems in implementing United Nations action against terrorism: first, the ineffectiveness of deterrence when terrorism is motivated by beliefs powerful enough to provoke suicide attacks; second, the risk that the rule of law will be undermined if criminal justice measures do not prevent terrorism. A prospective common solution is to develop aggressive and effective preventive measures explicitly drawn from rule of law standards. A number of preventive strategies, as well as one evidentiary measure and one international cooperation development, are discussed. The goal to be achieved is the integration of human rights guaranteed by the rule of law into a preventive criminal justice strategy. When terrorist violence is prevented rather than merely punished, and human rights are protected, respect for the rule of law will be not merely safeguarded, but enhanced